Green synthesis of copper nanoparticles using Cissus vitiginea and its antioxidant and antibacterial activity against urinary tract infection pathogens - Wu, Shuang; Rajeshkumar, Shanmugam; Madasamy, Malini; Mahendran, Vanaja (Artificial cells, nanomedicine, and biotechnology, 2020)
The green approachable of metal nanoparticles is treated to be an eco-friendly path and cost-effectiveness. In this present study, nano copper was synthesized profitably by Cissus vitiginea. The synthesized nano copper was used to evaluate the antioxidant and antibacterial activity against urinary tract infections pathogens. The resulting constructed nanoparticles were characterized by using ultraviolet spectroscopy absorbance around 370 nm. Scanning electron microscopy results showed the distribution of nanoparticles and particles sizes are found to be in the range of 5-20 nm. X-ray diffraction spectrum characteristic diffraction peaks for copper nanoparticles were observed at 2θ ranges 35.5 and 43.2° correspond to lattice planes (1 1 1) and (2 0 2), respectively. X-ray photoelectron spectroscopy shows that two distinct peaks at binding energy resulted that the chemical states of copper. The results serve the evidence that the green mediated nano copper might indeed be the potential source to treat urinary tract infections caused by E. coli, Enterococcus sp., Proteus sp. and Klebsiella sp. This fact-finding conclusion is that C. vitiginea leaf extract based green synthesis nano copper particles proved to effectively kill it or significantly inhibit activity contra to urinary tract infection pathogens and exhibit excellent antioxidant activity.